Oral estrogen leads to falsely low concentrations of estradiol in a common immunoassay. Issue 2 (9th February 2022) - Cirrincione, Lauren R; Crews, Bridgit O; Dickerson, Jane A; Krasowski, Matthew D; Rongitsch, Jessica; Imborek, Katherine L; Goldstein, Zil; Greene, Dina N
Abstract : Objectives: Recently, an estradiol immunoassay manufacturer (Beckman Coulter, USA) issued an 'important product notice' alerting clinical laboratories that their assay (Access Sensitive Estradiol) was not indicated for patients undergoing exogenous estradiol treatment. The objective of this analysis was to evaluate immunoassay bias relative to liquid chromatography tandem mass spectrometry (LC-MS/MS) in transgender women and to examine the influence of unconjugated estrone on measurements. Design: Cross-sectional secondary analysis. Methods: Estradiol concentrations from 89 transgender women were determined by 3 immunoassays (Access Sensitive Estradiol ('New BC') and Access Estradiol assays ('Old BC'), Beckman Coulter; Estradiol III assay ('Roche'), Roche Diagnostics) and LC-MS/MS. Bias was evaluated with and without adjustment for estrone concentrations. The number of participants who shifted between three estradiol concentration ranges for each immunoassay vs LC-MS/MS (>300 pg/mL, 70–300 pg/mL, and <70 pg/mL) was calculated. Results: The New BC assay had the largest magnitude overall bias (median: −34%) and was −40%, −22%, and −10%, among participants receiving tablet, patch, or injection preparations, respectively. Overall bias was −12% and +17% for the Roche and Old BC assays, respectively. When measured with the New BC assay, 18 participants shifted to a lower estradiol concentration range (vs 9 and 10 participants based on Roche or Old BC assays, respectively). Adjustment for estrone did not minimize bias. Conclusions: Immunoassay measurement of estradiol in transgender women may lead to falsely decreased concentrations that have the potential to affect management. A multidisciplinary health care approach is needed to ensure if appropriate analytical methods are available.